Variable Structure Adaptive Fuzzy And Neural Network Controllers For Facts Devices - V., Stella (2005)
This thesis presents new control strategies for the most versatile "Flexible AC Transmission Systems (FACTS)" devices, the UPFC (Unified Power Flow Controller) and STATCOM (Static Synchronous Compensator) which can be used to enhance system stability, voltage and power flow control. The various control strategies proposed in this thesis are briefly discussed.